Degenerative Spondylolisthesis: A Narrative Review - Akkawi, Ibrahim; Zmerly, Hassan (Acta Biomedica Atenei Parmensis, 2022)
Degenerative spondylolisthesis (DS) is a condition leading to the slippage of one vertebral body over the one below due to degenerative changes resulting in spinal stenosis and producing neurogenic claudication, with or without low back pain. DS prevalence is age and gender specific. Other risk factors mainly include a history of occupational driving, intense manual activity and sedentary work. Diagnosis for patients with DS include detailed history, physical examination and imaging through standing lateral radiographs and MRI. Most patients with symptomatic DS and absence of neurologic deficits should perform better with conservative treatment, whereas, patients with neurological symptoms, are more prone to undergo progressive functional deterioration without surgery. There is a lack of agreement on the best surgical management in patients with DS and symptomatic stenosis. There is a contradictory data that does not permit for a recommendation for or against the addition of fusion to decompression. There is also controversy on which fusion technique is best. Spinal minimally invasive surgery is a promising approach for DS promoting early recovery and enhanced quality of life by reducing skin incision, muscular damage and perioperative pain with significant improvements in clinical results and high satisfaction rates.